Research Progress of Aging-related MicroRNAs - Chen, Zhongyu; Li, Chenxu; Huang, Haitao; Shi, Yi-Ling; Wang, Xiaobo (Current stem cell research & therapy, 2024)
Senescence refers to the irreversible state in which cells enter cell cycle arrest due to internal or external stimuli. The accumulation of senescent cells can lead to many age-related diseases, such as neurodegenerative diseases, cardiovascular diseases, and cancers. MicroRNAs are short non-coding RNAs that bind to target mRNA to regulate gene expression after transcription and play an important regulatory role in the aging process. From nematodes to humans, a variety of miRNAs have been confirmed to alter and affect the aging process. Studying the regulatory mechanisms of miRNAs in aging can further deepen our understanding of cell and body aging and provide a new perspective for the diagnosis and treatment of aging-related diseases. In this review, we illustrate the current research status of miRNAs in aging and discuss the possible prospects for clinical applications of targeting miRNAs in senile diseases.